Soul, body, and survival : essays on the metaphysics of human persons - Corcoran, Kevin, 1964- (Cornell University Press, 2001)
How are soul and body related to one another? Are human beings immaterial souls, or complex physical organisms? Will we survive the death of our bodies? Does only the dualist view allow the possibility of life after death? This collection brings together cutting-edge research on the metaphysics of human nature and the possibility of post-mortem survival. Kevin Corcoran's collection, Soul, Body, and Survival, includes chapters from those who embrace traditional soul-body dualism, those who assert person-body identity, and those who propose entirely new views that fall outside the categories of monism and dualism. The first book to connect the metaphysics of persons with the belief in life after death, thus intersecting with theological as well as philosophical inquiry, it blurs the divide between metaphysics and the philosophy of mind.